Interesse e esforço: uma análise histórica a partir da teoria de John Dewey (1859-1952) - Buzin, Karina dos Santos de Moura (2021)
This academic research historically analyzed the categories of interest and effort based on the theory of John Dewey (1859-1852). For this purpose, a qualitative study was carried out, aiming at understanding the concept of interest and effort, based on the author's historical, political, social, and intellectual influences. The author's theoretical contribution to the categories was presented, and the interpretations of contemporary scholars about interest and effort were investigated. The main sources used to refer to Dewey's books: Life and Education (1978), How We Think (1979a), Democracy and Education (1979b), Experience and Education (1979c), and La opinión pública y sus problemas (2004). It was found that in contemporary History of Education there are Dewey's interpreters of the categories of interest and effort; therefore, a bibliographic review was carried out in textbooks on History of Education and/or Pedagogy, in theses, dissertations, and scientific articles available on the Internet or published in books. The texts contained in the title, abstract, keywords, or in the body of the text the following descriptors: interest, effort, and John Dewey were selected. We also studied the authors who, like Dewey, are considered classics in educational studies and who discussed the selected categories: Kant (1724-1804), Herbart (1776-1841), Montessori (1870-1952), Decroly (1871-1932), Claparède (1873-1940), Kilpatrick (1871-1965), Krupskaya (1869- 1939), Vigotski (1896-1934), Makarenko (1888-1939), and Gramsci (1891-1937). Subsequently, we sought to understand Dewey's categories of interest and effort, relating them to his theory of education and democratic society. Based on the studies carried out, it was noted that Dewey, observing the numerous social transformations of his time, as well as the educational debates about the need for a new way of thinking about teaching, made possible great contributions to education. About the categories of interest and effort, it was verified that they are historically discussed in education, and, from a conciliation vision, Dewey composes them as an important part of the constitution of a democratic society.